Severe Toxicity Following Combined Overdose of Verapamil, Atenolol, Propafenone, and Simvastatin in a Suicidal Attempt: A case study - Sugianto Parulian Simanjuntak*; Erwin Pradian; Ricky Aditya (SVU - International Journal of Medical Sciences, 2023)
Background: Overdoses with cardiovascular-active drugs are associated with significant morbidity and mortality. Intoxications involving multiple antiarrhythmic agents have been documented in several case reports, yet an instance of intentional overdose with three varieties of antiarrhythmics concomitant with simvastatin has not been previously reported. We report a rare case of severe toxicity from combined overdose of verapamil, atenolol, propafenone, and simvastatin, leading to resistant hypotension and total AV block. Case report: A 25-year-old male patient was brought to the Emergency Department (ED) with decreased consciousness and vomiting following a suicide attempt. He had a documented medical history of depression but had not previously attempted suicide. Laboratory findings indicated metabolic acidosis, severe hypoxemia, acute kidney injury (AKI) and elevated liver enzymes. Prompt resuscitation measures, including high-dose inotropic infusions and intensive care unit (ICU) admission, were initiated. Hemodialysis led to significant improvement, and successful extubation was achieved on the second day of ICU care. Through aggressive medical intervention, the patient's hemodynamic status normalized, negating the need for a pacemaker. He was extubated on ICU day two and discharged on day eight. Conclusion: This case underscores the clinical challenges associated with polypharmacy overdoses, their potential cardiac complications, and the crucial importance of aggressive and early intervention strategies.